Metabolomic analysis of halotolerant endophytic bacterium Salinivibrio costicola isolated from Suaeda maritima (L.) dumort - Lee, Jaeyoun; Um, Soohyun; Kim, Seung Hyun (Frontiers in Molecular Biosciences, 2022)
In this study, Salinivibrio costicola strain was isolated from Suaeda maritima (L.) Dumort. collected in Sinan, Republic of Korea. The endophytic characteristic of Gram-negative bacterium, S. costicola, was verified with metagenomics sequencing of S. maritima. S. costicola was cultivated for 3 days in liquid medium with 3.3% of sea salt and analyzed statistical assay with metabolites produced by S. costicola cultured in five different bacterial cultivation media. From the bacterial cultures, polyhydroxybutyric acid derivatives were detected by HRMS, then we isolated three major compounds by HPLC. The chemical structures of the compounds were elucidated by NMR and MS spectroscopic analyses. The relationship of the compounds was confirmed with GNPS that showed clustering of the compounds. From the extract of S. maritima, polyhydroxybutyric acid derivative produced by S. costicola was detected being accumulated in the host plant.